PROSES PERUMUSAN KEBIJAKAN PUBLIK DAN IMPLIKASINYA BAGI PENYELENGGARAAN KEPEMERINTAHAN YANG BAIK DI DAERAH - Damayanti, Kania (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2005)
Public policy formulation process can be seen as theresearch process of public policycovering the steps of identifying problems in thesociety,setting up relationship model, goal and target setting of problem solving, developing policy alternatives, setting up criteria for selection and making recommendations. In relation to good governance, public policy process both in central and local government should be able to reflect the characteristics of good governance. Public policy formulation process in regions requires the improvement of the local government agents competency, both the executives and the legislatives in terms of management and public policy analysis and the change in mental model.